Applying Social Cognitive Theory To Understand Factors Influencing Adolescent Physical Activity: A Systematic Review - Maria Jia Fernandez; Makhfudli Makhfudli; Rista Fauziningtyas (Jurnal Ners, 2025)
Physical activity can improve the physical and mental health of adolescents so it is an important aspect for adolescents. However, data from around the world show that adolescents have consistently experienced a decline in physical activity. Less than 20% of adolescents meet WHO physical activity standards. Many studies have found factors that affect physical activity, but only a few studies have combined all of these factors into one complete theory. This systematic review aims to identify and synthesize the main factors that affect physical activity among adolescents according to social cognitive theory. This systematic review refers to the PRISMA 2020 guidelines, with inclusion criteria for healthy adolescents aged 10-24 years, articles included in English published in 2020-2025, were quantitative studies using cross-sectional study study research design and physical activity as independent variables using a theoretical social-cognitive approach. The quality of the study assessment by JBI critical assessment tool and used a narrative approach based on the theme of the social cognitive theory. Social cognitive theory is a solid basis for determining the complex components that influence adolescent physical activity. Interventions used to improve adolescent physical activity should prioritize self-efficacy social support an integrated and interacting family, school and community Kata Kunci: Physical activity, Social cognitive theory, Adolescents, cross-sectional study